Application limestone forms and doses for Alfalfa in no-tillage system - Toffolli, Letícia Cristina; Assmann, Tangriani; Assmann, Alceu; Cassol, Luís; Toffolli, Rodolfo; Nicola, Vinícius; Ferrazza, Jussara (Revista Ciência Agronômica, 2014)
Alfalfa (Medicago sativa L.) requires good soil fertility. Brazil is characterized by acidic soils which reduce the potential of the crop. Generally, liming is incorporated into the soil, but in tillage systems it is inadvisable. This study aimed to evaluate the effects of the lime application method and dose on pH, Al+3, V % and Ca+Mg in the soil and on dry matter yield of alfalfa cultivated under a consolidated no-tillage system. The experiment was conducted at the Experimental Station of Paraná Agronomic Institute, located in Pato Branco city, in Paraná state. The plots consisted of the types of lime application (plowing+harrowing, subsoil and surface), the sub-plots was the lime dose (0, 2, 4, 6 and 8 Mg ha-1) and the sub-sub-plots were the sampled soil depth (0-5; 5-10; 10-20 and 20-30 cm). The results show the application of lime, even superficially, caused increases in pH, concentration of Ca and Mg and base saturation of the soil, while also reducing the concentration of Al, especially in the surface layers of the soil. The practice of plowing and harrowing or of subsoiling, with the aim of lime incorporation in a consolidated no-tillage system is unnecessary. If it is required, the application of lime to the soil should be done superficially for alfalfa cultivated in this system.